Eksistensi Aktivitas Kebudayaan dalam Mengawal Peradaban Kehidupan Sosial: Tradisi Sekatenan Keraton Yogyakarta Perspektif Teori Solidaritas Emile Durkheim - Muhammad Sultan Latif; Muhammad Syafi'i Ahmad Ar. (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article discusses how the existence of cultural activities especially is the tradition of Sekatenan Kraton Yogyakarta in guarding the civilization development of social life, trough Emile Durkheim's perspective. The method used is analytic-critic-observative. Sekatenan Kraton Yogyakarta when viewed from the perspective of Emile Durkheim's solidarity theory, there are there factors that drive this tradition. First, the existence of religious doctrine. Second, there is the involvement of every social level line. Third, there is an interest in the economic sector, namely peddling people's entertainment and some cheap merchandise to residents which was held on 1-10 Rabi'ul awwal. Based on these three elements, the Sekatenan Kraton Yogyakarta tradition provides several contributions in building a civilization of social life. First, improve spirit of religious quality. Second, as a manifestation in brotherhood strengthening and improve the relationships quality between each other. Third, improve the economics quality of the Yogyakarta citizens.